Method for measuring size of high-temperature oxidation mass point in steel surface crack
By using scanning electron microscope automatic analysis function near the steel surface cracks combined with component screening, measuring the size of high-temperature oxidation particles, the problems of low efficiency and data distortion in the existing technology are solved, and more efficient and accurate crack analysis is achieved.
Patent Information
- Application Number
- CN202411889804.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art when measuring the size of high-temperature oxidation particles near cracks on the surface of steel, the efficiency is low and the data is distorted, making it difficult to accurately judge the specific process of crack generation.
The automatic scanning electron microscopy analysis function was used to combine the oxidized particle components, and the data of the sum of the mass of (Si+Mn+Fe) atomic mass/sum of the sum of the total atomic mass of the element ≥60% and the sum of the mass of (Si+Mn) atomic mass/(Si+Mn+Fe) atomic mass was screened out, and the average size of the high-temperature oxidized particles was calculated.
The efficiency and accuracy of oxidation particle size measurement are improved, the interference of non-metallic inclusions and iron oxide sheets is avoided, and the integrity of crack oxidation particle size characterization is enhanced.
Smart Images

Figure CN119619206A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel surface crack research, and in particular to a method for measuring the size of high-temperature oxidized particles in steel surface cracks. Background Art
[0002] The production process of steel products includes continuous casting of molten steel, heating of ingots, and rolling into finished products. However, when or after the steel solidifies, surface cracks may appear on its surface due to various reasons such as inapplicable mold protection slag, poor cooling of secondary cooling water, excessive straightening force, inappropriate heating temperature of the steel billet, and rolling scratches. Steel products with cracks will not disappear during the subsequent series of processing such as forging, extrusion, and drawing, and will cause great harm to the surface, service life, and performance of the final metal products. Therefore, it is very necessary to control the surface cracks of steel products. The main constituent elements of steel products are Fe, Si, Mn, Cr and other elements. When steel is under oxidizing conditions (such as in the atmosphere) and experiences high temperatures, oxygen atoms will diffuse into the steel and react with solute elements Si, Mn, Cr and other elements in the steel to form corresponding oxides; since this reaction only occurs at higher temperatures, the corresponding products are called high-temperature oxidation particles. When crack defects appear in steel under high temperature conditions (such as cracking in the crystallizer), the area near the crack meets high temperature and oxidation conditions, so high-temperature oxidation particles will appear near the crack.
[0003] At present, the conventional crack control scheme is to roughly infer the possible cause of the crack by the morphology of the crack on the final product and the degree of decarburization near it. However, this method is relatively rough, and the efficiency of solving problems in actual production is extremely low, and misjudgment often occurs. Therefore, a more detailed analysis and judgment is needed for the specific generation stage of cracks in the process of continuous casting, heating, rolling, etc. Among them, one of the key issues is the size measurement of high-temperature oxidation particles near the crack.
[0004] Obtaining the size data of high-temperature oxidation particles near cracks is critical for inferring which production process the cracks originated from. The higher the temperature at which the cracks are generated, the larger the size of the corresponding oxidation particles near the cracks; therefore, the size of the oxidation particles can correspond to the temperature history of the steel, find the location of the cracks, and provide the most basic direction for the subsequent crack resolution. There are two main conventional methods for measuring the size of high-temperature oxidation particles near cracks: Method 1 is manual measurement one by one, which is labor-intensive because there are hundreds or thousands of high-temperature oxidation particles near the cracks. The measurement process requires the confirmation of the oxidation particle composition one by one (to eliminate the interference of non-oxidation particle substances as much as possible), and then the size measurement is performed, and the measurement efficiency is very low. Method 2 is to use image processing software (such as IMAGE PLUS PRO) for measurement. The main process is to first take pictures of the oxidized particles near the crack, then piece them together into a complete image, and then use image recognition software to identify them according to the pixel grayscale; this method improves the measurement efficiency compared to method 1, but because the only basis for the image recognition software to determine whether it is an oxidized particle is the pixels in the image that are different from the iron matrix, it is easy to identify foreign matter, inclusions, iron oxide scale, scratches, etc. as oxidized particles (all gray-black phases close to the color of oxidized particles), and the size of the oxidized particles finally obtained is in a fluctuating and uncontrollable state. In addition, the above two measurement methods do not consider the crack opening temperature during measurement, and the measurement position of the oxidized particles at the crack is randomly selected. The actual crack opening degree is different, which will lead to differences in the size of the oxidized particles. Therefore, the size of the oxidized particles finally obtained is further uncontrolled.
[0005] The present invention takes into account the different characteristics of oxidized particle sizes under different crack opening widths, utilizes the automatic analysis function of a scanning electron microscope, and combines the oxidized particle composition to effectively avoid interference from non-metallic inclusions and foreign matter such as oxidized iron scale. Compared with the traditional manual measurement of oxidized particle size or the use of image processing software pixels to identify the oxidized particle size, the recognition efficiency and recognition accuracy are improved. At the same time, the combination of oxidized particle sizes with different opening degrees improves the completeness of the overall crack oxidized particle size characterization. Summary of the invention
[0006] Aiming at the shortcomings of the existing methods, the present invention solves the problems of large workload and low efficiency in the current manual measurement of oxidation particles; image recognition software measurement data distortion and other problems, and finally obtains the oxidation particle size data efficiently, providing a reference basis for the origin of cracks. At the same time, the quantitative requirements for the measurement position of oxidation particles are given, providing a new solution for the validity of oxidation particle size data.
[0007] The technical solution adopted by the present invention is: a method for measuring the size of high-temperature oxidized particles in cracks on the surface of steel includes the following requirements: (1) Sample preparation requires cutting in the direction perpendicular to the crack, and finally grinding and polishing to make a metallographic sample that meets the requirements of SEM observation; (2) Crack scanning: Use the automatic energy spectrum function of the scanning electron microscope to scan the crack oxidation particles and obtain the composition and size data of the scanned material.
[0008] Furthermore, the scanning area is required to be 0.01mm 2 ~0.05mm 2 ; The scanning magnification is selected as 2800 times ~ 3200 times; the scanning size is ≥ 0.05μm; the scanning area is the crack opening width of 75~85μm and 3μm~8μm; The crack opening width is the width inside the crack. Different crack opening widths in the present invention refer to the widths at different depths inside the crack.
[0009] (3) Data processing: judging whether it is an oxidized particle based on the composition characteristics of the scanned material; Furthermore, it is required to screen the sum of the atomic mass of (Si+Mn+Fe) / the sum of the total atomic mass of the elements ≥ 60%; the sum of the atomic mass of (Si+Mn) / the sum of the atomic mass of (Si+Mn+Fe) ≥ 20%, which is determined to be an oxidized particle. (4) Filter the data of oxidation particle size and calculate the average size of high-temperature oxidation particles.
[0010] For sample preparation, the cutting direction of the vertical crack is required, and finally after grinding and polishing, it is made into a metallographic sample that meets the requirements of scanning electron microscope observation. The reason is that compared with parallel crack cutting, vertical crack cutting can obtain all information of the crack cross section, such as depth, opening, decarburization, oxidation particle distribution and other information, so the crack cutting direction needs to be vertical crack cutting. The key point of the present invention is to measure the size of oxidation particles. Since the size of most oxidation particles is distributed in 0.1μm~0.8μm, conventional optical microscopes do not have the observation capability (≤1000 times), and a scanning electron microscope is required to observe more clearly (≥2000 times). Therefore, it is necessary to make the crack sample into a mirror metallographic sample that can be used for scanning electron microscope observation.
[0011] For crack scanning, the requirement of using the automatic energy spectrum function of the scanning electron microscope to scan the oxidation particles in the crack is that the number of oxidation particles near the crack ranges from hundreds to thousands, and the workload of manually confirming the composition and measuring the size one by one is too large. Therefore, it is necessary to use a scanning electron microscope with automatic energy spectrum scanning function to identify the composition and measure the size at the same time. Finally, the composition characteristics of the scanned material are used as the basis to judge whether it is an oxidation particle, and the oxidation particle size data is obtained based on the corresponding size.
[0012] The scanning area is required to be 0.01mm2 ~0.05mm 2 ; The scanning magnification is selected as 2800 times ~ 3200 times; The requirement of scanning size ≥ 0.05μm is because: based on the premise that the size distribution of oxidation particles is mostly 0.1μm ~ 0.8μm, in order to ensure that the oxidation particles can be detected as comprehensively as possible, the detection starting size is set to ≥ 0.05μm. If the starting size is < 0.05μm, the detection progress will be too slow and the time will be too long. When using the automatic energy spectrum scanning function of the scanning electron microscope, in order to ensure that small-sized materials such as oxidation particles can be accurately detected by the electron microscope, the magnification is selected to be 2800 times ~ 3200 times. If the magnification is greater than 3200 times, the detection progress will be slow, and if the magnification is less than 2800 times, there is a possibility of missed detection. On the other hand, since the width of the high-temperature oxidation particles in the vertical crack direction is mostly 20μm to 400μm, in order to ensure that all oxidation particles in the vertical crack direction can be detected under a field of view of about 3000 times, the detection area is controlled to 0.01mm 2 ~0.05mm 2 .
[0013] The reason for the requirement of crack opening width of 75~85μm and 3μm~8μm in the scanning area is that: in the crack depth direction, due to different crack openings, the cracks receive different degrees of oxidation, which ultimately affects the size of the cracks; on the other hand, the difference in crack oxidation degree will lead to differences in the thickness of the iron oxide scale near the cracks, so it is necessary to quantitatively give reasonable crack opening width requirements. A complete crack is mainly composed of main cracks and microcracks. There is a certain difference in the size of the oxidation particles of the two. Therefore, it is necessary to measure the oxidation particles near the cracks with different opening widths to characterize the size characteristics of the oxidation particles of this crack. If the crack opening is greater than 85μm, although it is a main crack, the crack surface is too severely oxidized, and the iron oxide scale covers the oxidation particles, resulting in the measured oxidation particles being unrepresentative; if the crack opening is less than 75μm, it does not have the characteristics of a main crack, so the opening of the main crack oxidation particles is optimally 75μm~85μm. For microcracks, if the crack opening is greater than 8μm, the crack opening is large and does not have the characteristics of a microcrack; if the crack opening is less than 3μm, the oxidation is close to the forefront area, the oxidation ability is extremely weak, and it does not have the major prerequisite for crack analysis. Therefore, the optimal opening of the microcrack oxidation particle is 3μm~8μm. After measuring the size of the oxidation particles at the cracks with these two opening widths, the size distribution of the overall oxidation particles of the entire crack can be fully characterized.
[0014] For data processing, it is required to screen the sum of the atomic masses of (Si+Mn+Fe) / the sum of the total atomic masses of the elements ≥60%; the sum of the atomic masses of (Si+Mn) / the sum of the atomic masses of (Si+Mn+Fe) ≥20%. The reason is that the main components of the oxidized particles are FeO-SiO2 and MnO-SiO2. In addition to the oxidized particles, the actual metallographic samples also contain inclusions, foreign matter (such as dirt, water stains, etc.), iron oxide scale and other substances. Therefore, component screening is required to ensure that the statistical data is the oxidized particle size data. The sum of the atomic masses of (Si+Mn+Fe) / the sum of the total atomic masses of the elements ≥60% can ensure that the corresponding scanned substances are SiO2, MnO, and FeO substances, thereby excluding substances such as foreign matter, CaO-Al2O3 inclusions, and MgO-Al2O3 inclusions. However, there is still a risk that substances such as oxidized iron scale cannot be excluded; combined with the requirement that the sum of the atomic masses of (Si+Mn) / the sum of the atomic masses of (Si+Mn+Fe) ≥20%, oxidized iron scale substances can be excluded. Finally, it can be determined that the screened substances are oxidized particles.
[0015] The beneficial effects of the present invention are as follows: by taking into account the different characteristics of the sizes of oxidized particles at different crack opening widths and combining the distribution characteristics of the oxidized particle components, the interference of non-metallic inclusions and foreign matter such as oxidized iron scale is effectively avoided. Compared with the traditional manual measurement of the size of oxidized particles or the use of image processing software pixels to identify the size of oxidized particles, the recognition efficiency and recognition accuracy are improved. At the same time, the combination of the sizes of oxidized particles with different openings improves the completeness of the overall crack oxidized particle size characterization. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic diagram of the process of measuring the size of oxidation particles of the present invention; Figure 2 This is the morphology of the oxidation particles corresponding to the crack opening width of 80 μm and 5 μm in Example 1 of the present invention (scale: 7.15 μm); Figure 3 The comparison of the size of the main crack oxidized particles (a) and the size of the micro crack oxidized particles (b) of the present invention; Figure 4 The comparison of the size variance of the main crack oxidized particles (a) and the comparison of the size variance of the microcrack oxidized particles (b) of the present invention. DETAILED DESCRIPTION
[0017] The present invention is further described below in conjunction with the accompanying drawings and embodiments. This figure is a simplified schematic diagram, which only illustrates the basic process of the present invention in a schematic manner and is not intended to limit the present invention.
[0018] Take the artificial prefabricated crack of 40Cr steel as an example to test, the crack opening at the top is controlled between 90μm and 300μm, and the laboratory resistance furnace is used to heat without protective atmosphere, the heating temperature is 1200℃, the temperature is kept for 50min, and the sample is air-cooled after being taken out, and the size of the oxidized particles is measured. The standard composition requirements of steel grades are shown in Table 1 below.
[0019] Table 1 Standard composition of 40Cr steel, % C Si Mn P S Cu Cr Mo 0.37~0.44 0.17~0.37 0.5~0.8 ≤0.03 ≤0.03 ≤0.2 0.8~1.1 ≤0.1 The main production processes of each process are as follows (see the process diagram Figure 1 ): (1) Sample preparation: cutting in the direction perpendicular to the crack, and finally grinding and polishing to make a metallographic sample that meets the requirements of SEM observation; (2) The methods for measuring the size of oxidation particles are divided into: ①Use the automatic energy spectrum function of the scanning electron microscope to scan the crack oxidation particles. The scanning area is 0.02mm 2 ; The scanning magnification selection is divided into: a. 3000 times, b. 2000 times, c. 6000 times; the scanning size is ≥ 0.05μm; the scanning area is divided into crack opening width: a. 80μm, b. 50μm, c. 120μm and d. 5μm, e. 1μm, f. 15μm. The scanning data screening method is divided into: a. The sum of the atomic mass of (Si+Mn+Fe) / the sum of the atomic mass of the elements is ≥ 60%; the sum of the atomic mass of (Si+Mn) / the sum of the atomic mass of (Si+Mn+Fe) is ≥ 20%; b. No screening; c. Only the sum of the atomic mass of (Si+Mn+Fe) / the sum of the atomic mass of the elements is ≥ 60%; d. Only the sum of the atomic mass of (Si+Mn) / the sum of the atomic mass of (Si+Mn+Fe) is ≥ 20%.
[0020] ②Manually perform composition detection and size measurement on each oxidized particle.
[0021] ③ Use a scanning electron microscope to take pictures of the oxidized particles on one side of the crack; the magnification is selected as 3000 times; the scanning area is the crack opening width of 80μm and 5μm. After the pictures are sorted, the size of the oxidized particles is counted using IPP software.
[0022] (3) Obtain the size of high-temperature oxidation particles and calculate the average size of oxidation particles.
[0023] Statistics: Statistics on the average size of oxidation particles, statistics on the time of each scheme, statistics on the data stability of different schemes. Example 1
[0024] The automatic energy spectrum function of the scanning electron microscope is used to scan the crack oxidation particles. The scanning area is 0.02mm 2 ; The scanning magnification is selected as 3000 times; The scanning size is ≥0.05μm; The scanning area is the crack opening width of 80μm and 5μm. The scanning data screening method is to screen the sum of the atomic mass of (Si+Mn+Fe) / the sum of the total atomic mass of the elements ≥60%; the sum of the atomic mass of (Si+Mn) / the sum of the atomic mass of (Si+Mn+Fe) ≥20%. The morphology of the oxidation particles near the main and micro cracks is shown in Figure 2 (a) and Figure 2 (b).
[0025] A total of 3 different cracks were found, with opening widths of 80 μm and 5 μm, and the scheme of Example 1 was repeated to measure the size of the oxidation particles to determine the stability of the oxidation particle size data. Comparative Example 1
[0026] The automatic energy spectrum function of the scanning electron microscope is used to scan the crack oxidation particles. The scanning area is 0.02mm 2 ; The scanning magnification is selected as 2000 times; the scanning size is ≥0.05μm; the scanning area is the crack opening width of 80μm and 5μm. The scanning data screening method is to screen the sum of the atomic mass of (Si+Mn+Fe) / the sum of the total atomic mass of the elements ≥60%; the sum of the atomic mass of (Si+Mn) / the sum of the atomic mass of (Si+Mn+Fe) ≥20%.
[0027] A total of 3 different cracks were found, with opening widths of 80 μm and 5 μm, and the size of the oxidized particles was measured by repeating the scheme of Comparative Example 1 to determine the stability of the oxidized particle size data. Comparative Example 2
[0028] The automatic energy spectrum function of the scanning electron microscope is used to scan the crack oxidation particles. The scanning area is 0.02mm 2 ; The scanning magnification is selected as 6000 times; The scanning size is ≥0.05μm; The scanning area is the crack opening width of 80μm and 5μm. The scanning data screening method is to screen the sum of the atomic mass of (Si+Mn+Fe) / the sum of the total atomic mass of the elements ≥60%; the sum of the atomic mass of (Si+Mn) / the sum of the atomic mass of (Si+Mn+Fe) ≥20%.
[0029] A total of 3 different cracks were found, with opening widths of 80 μm and 5 μm, and the comparative example 2 was repeated to measure the size of the oxidized particles to determine the stability of the oxidized particle size data. Comparative Example 3
[0030] The automatic energy spectrum function of the scanning electron microscope is used to scan the crack oxidation particles. The scanning area is 0.02mm 2; The scanning magnification is selected as 3000 times; The scanning size is ≥0.05μm; The scanning area is the crack opening width of 50μm and 1μm. The scanning data screening method is to screen the sum of the atomic mass of (Si+Mn+Fe) / the sum of the total atomic mass of the elements ≥60%; the sum of the atomic mass of (Si+Mn) / the sum of the atomic mass of (Si+Mn+Fe) ≥20%.
[0031] A total of 3 different cracks were found, with opening widths of 50 μm and 1 μm, and the comparative example 3 was repeated to measure the size of the oxidized particles to determine the stability of the oxidized particle size data. Comparative Example 4
[0032] The automatic energy spectrum function of the scanning electron microscope is used to scan the crack oxidation particles. The scanning area is 0.02mm 2 ; The scanning magnification is selected as 3000 times; The scanning size is ≥0.05μm; The scanning area is the crack opening width of 120μm and 15μm. The scanning data screening method is to screen the sum of the atomic mass of (Si+Mn+Fe) / the sum of the total atomic mass of the elements ≥60%; the sum of the atomic mass of (Si+Mn) / the sum of the atomic mass of (Si+Mn+Fe) ≥20%.
[0033] A total of 3 different cracks were found, with opening widths of 120 μm and 15 μm, and the comparative example 4 was repeated to measure the size of the oxidized particles to determine the stability of the oxidized particle size data. Comparative Example 5
[0034] The automatic energy spectrum function of the scanning electron microscope is used to scan the crack oxidation particles. The scanning area is 0.02mm 2 ; The scanning magnification is selected as 3000 times; The scanning size is ≥ 0.05μm; The scanning area is the crack opening width of 80μm and 5μm. The method for screening the scanned data is not screening.
[0035] A total of 3 different cracks were found, with opening widths of 80 μm and 5 μm, and the comparative example 5 was repeated to measure the size of the oxidized particles to determine the stability of the oxidized particle size data. Comparative Example 6
[0036] The automatic energy spectrum function of the scanning electron microscope is used to scan the crack oxidation particles. The scanning area is 0.02mm 2 ; The scanning magnification is selected as 3000 times; The scanning size is ≥0.05μm; The scanning area is the crack opening width of 80μm and 5μm. The method for screening the scanned data is to only screen the sum of the atomic mass of (Si+Mn+Fe) / the sum of the total atomic mass of the elements ≥60%.
[0037] A total of 3 different cracks were found, with opening widths of 80 μm and 5 μm, and the comparative example 6 was repeated to measure the size of the oxidized particles to determine the stability of the oxidized particle size data. Comparative Example 7
[0038] The automatic energy spectrum function of the scanning electron microscope is used to scan the crack oxidation particles. The scanning area is 0.02mm 2 ; The scanning magnification is selected as 3000 times; The scanning size is ≥0.05μm; The scanning area is the crack opening width of 80μm and 5μm. The method for screening the scanned data is to only screen the sum of the atomic mass of (Si+Mn) / the sum of the atomic mass of (Si+Mn+Fe) ≥20%.
[0039] A total of 3 different cracks were found, with opening widths of 80 μm and 5 μm, and the comparative example 7 was repeated to measure the size of the oxidized particles to determine the stability of the oxidized particle size data. Comparative Example 8
[0040] The composition and size of each oxidized particle are manually detected and measured.
[0041] A total of 3 different cracks were found, with opening widths of 80 μm and 5 μm, and the method of comparative example 8 was repeated to measure the size of the oxidized particles to determine the stability of the oxidized particle size data. Comparative Example 9
[0042] The oxidized particles on one side of the crack were photographed using a scanning electron microscope; the magnification was selected to be 3000 times; the scanning area was the crack opening width of 80μm and 5μm. After the pictures were sorted, the size of the oxidized particles was counted using IPP software.
[0043] A total of 3 different cracks were found, with opening widths of 80 μm and 5 μm, and the scheme of comparative example 9 was repeated to measure the size of the oxidized particles to determine the stability of the oxidized particle size data.
[0044] Statistics The statistics, variance and time of the oxidation particle size are shown in Table 1 and Figure 3 , Figure 4: Taking Comparative Example 8 (manual measurement one by one) as the control group, the main crack and microcrack data of Example 1 are close to those of Example 8. Taking the ±10% deviation of the size of the oxidized particles in Comparative Example 8 as the benchmark, the data within the deviation is considered reliable, then the main cracks of 0.477μm~0.583μm are considered reliable, and the microcracks of 0.423μm~0.517μm are considered reliable; only Comparative Example 6 (compared with Example 1, Comparative Example 6 is only a partial data screening) meets both conditions. However, the variances of the main and microcrack sizes in Comparative Example 6 are 0.035 and 0.047, respectively, which are larger than the 0.017 and 0.015 variances of the main and microcracks in Example 1, indicating that although the average size is relatively reliable when the method of Comparative Example 6 is adopted, the data fluctuates greatly and still cannot meet the requirements of data stability. The mean values of the oxidized particle sizes measured in Comparative Examples 2~5, 7, and 9 all exceed the data deviation of the control group by ±10%, and their values themselves are not reliable.
[0045] Compared with Example 1, the data of Comparative Example 8 were measured and confirmed manually one by one, because it is believed that the data of Comparative Example 8 is more reliable. However, Comparative Example 8 takes 6 hours, while Example 1 only takes 1.5 hours. Therefore, although the data accuracy and stability of Comparative Example 8 are higher, the efficiency is too low to meet the actual application of industrial production.
[0046] Table 1 Oxidation particle size (μm) and variance of examples and comparative examples
[0047] Note: Main size (size of high temperature oxidation particles on the main crack side, μm), micro size (size of high temperature oxidation particles on the micro crack side, μm), main variance (variance of size of high temperature oxidation particles on the main crack side), micro variance (variance of size of high temperature oxidation particles on the micro crack side).
[0048] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for measuring the size of high temperature oxidation particles in cracks on the surface of steel, characterized in that: The following steps are involved: (1) Sample preparation: Cut vertically in the crack direction to prepare metallographic samples; (2) Crack scanning: Use the automatic energy spectrum function of the scanning electron microscope to obtain the composition and size data of the scanned material; (3) Data processing: Determine whether it is an oxidized particle based on the composition characteristics of the scanned material; (4) The size data of oxidation particles are screened and the average size of high-temperature oxidation particles is calculated.
2. The method for measuring the size of high temperature oxidized particles in cracks on the surface of steel according to claim 1, characterized in that: The sample preparation in step (1) requires cutting in the direction perpendicular to the crack, and finally grinding and polishing to produce a metallographic sample that meets the requirements of SEM observation.
3. The method for measuring the size of high temperature oxidized particles in cracks on the surface of steel according to claim 1, characterized in that: The crack scanning area in step (2) is the crack opening width of 75-85 μm and 3-8 μm.
4. The method for measuring the size of high temperature oxidized particles in cracks on the surface of steel according to claim 3, characterized in that: The scanning area of the crack scan in step (2) is required to be 0.01 mm 2 ~0.05mm 2 ; The scanning magnification is selected as 2800 times ~ 3200 times; the scanning size is ≥ 0.05μm.
5. The method for measuring the size of high temperature oxidized particles in cracks on the surface of steel according to claim 1, characterized in that: The basis for judging the oxidized particles in step (3) is that the sum of the atomic masses of the component characteristics (Si+Mn+Fe) / the sum of the total atomic masses of the elements is ≥60%; the sum of the atomic masses of (Si+Mn) / the sum of the atomic masses of (Si+Mn+Fe) is ≥20%, that is, it is judged as an oxidized particle.